Rotating Shifts Negatively Impacts Health and Wellness Among Intensive Care Nurses. (May 2019) - Imes, Christopher C.; Chasens, Eileen R.
The impact of shift work on sleep and health has been examined in the past, but most studies utilized cross-sectional designs relying on between-subject differences. The purpose this study was to examine the within-subject differences in self-report measures of health and wellness among a group of nurses engaged in rotating shifts. Patient-Reported Outcomes Measurement Information System (PROMIS) measures, collected post-day and post-night shift, were used to assess health, sleep disturbances and sleep-related impairment, fatigue, emotional distress (anger), satisfaction with social roles outside of work, and applied cognitive abilities. Among the sample of 23 White, mostly female (91.3%) nurses, all PROMIS measures were worse indicting lower health and wellness after working night shifts compare to after working day shifts ( p values from .167 to < .001). During both time points of assessment, sleep-related impairment was highly correlated with greater emotional distress, greater fatigue, and worse memory and concentration. Study findings support prior studies that shift work can negatively impact health and wellness.